Anti-corrosion, anti-fouling and anti-drag composite coating as well as preparation method and application thereof
Through the multi-layer structure-designed anti-corrosion and anti-fouling resistance reduction composite coating, the use of materials such as charged polymers and two-dimensional nanosheets, the problem of difficult to effectively control substrate corrosion and friction resistance in marine environments in the existing technology is solved, and longer-term equipment protection and sustainable marine transportation are achieved.
Patent Information
- Application Number
- CN202510406292.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-02
AI Technical Summary
When the prior art deals with complex and changeable marine environments, it is difficult to effectively prevent the corrosion of the substrate, and flexible drag reduction technology is difficult to maintain effective performance under long-term seawater immersion.
The anti-corrosion, anti-fouling and drag-reducing composite coating designed with a multi-layer structure, including the base layer, corrosion barrier layer, connecting layer and flexible anti-fouling layer. Through the combination of materials such as charged polymers and two-dimensional nanosheets, the strong interface combination of each layer and the coordinated enhancement of anti-corrosion and drag-reducing functions are achieved.
It has achieved effective prevention of substrate corrosion and reduced friction resistance in complex marine environments, extended the service life of ships and marine facilities, and promoted the sustainable development of the marine transportation and water treatment industries.
Smart Images

Figure CN119912856A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of marine coating protection, and specifically relates to an anti-corrosion, anti-fouling and drag-reducing composite coating and a preparation method and application thereof. Background Art
[0002] In today's industrial field, the application of anti-corrosion and drag reduction functional coatings has become a technology that has attracted much attention. With the acceleration of industrialization and the improvement of environmental protection awareness, the demand for anti-corrosion and friction resistance reduction in various fields has become increasingly urgent. Especially in marine transportation, marine engineering, shipbuilding and water treatment industries, marine organisms and seawater corrosion have brought serious problems to navigation bodies. In response to this challenge, researchers continue to explore innovative anti-corrosion and drag reduction functional coating technologies. By combining anti-corrosion materials with drag reduction technology, long-term protection of equipment and ship surfaces and reduction of friction resistance can be achieved. At present, flexible drag reduction technology is a key research direction in drag reduction technology. Its drag reduction mechanism relies on the flexible effect to suppress and absorb the wave changes of water pressure and delay the transition from laminar flow to turbulent flow, thereby achieving an effective drag reduction effect. However, in practical applications, it is difficult to cope with complex and changing environments relying solely on flexible mechanisms, such as the corrosion of the substrate under long-term immersion in seawater. Through multi-layer structural design, a variety of special functional compounds are effectively integrated together to achieve the goal of synergistically enhanced anti-corrosion and drag reduction functions. This is an innovative idea. In practical applications, this multifunctional coating can effectively cope with the changing environmental conditions of the ocean, extend the service life of ships and marine facilities, and promote the sustainable development of the marine transportation and water treatment industries. In the future, with the continuous advancement of science and technology and the innovation of materials engineering, anti-corrosion and drag-reducing functional coatings will continue to grow and develop, bringing more innovation and economic benefits to the industry. Therefore, the application prospects of this coating in various fields are very broad, providing important technical support and guarantee for us to create a cleaner and more efficient industrial environment. Summary of the invention
[0003] The main purpose of the present invention is to provide an anti-corrosion, anti-fouling and drag-reducing composite coating and a preparation method and application thereof, so as to overcome the deficiencies of the prior art.
[0004] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: The embodiment of the present invention provides an anti-corrosion, anti-fouling and drag-reducing composite coating, which comprises: a base layer, a corrosion barrier layer, a connecting layer and a flexible anti-fouling layer sequentially formed on the surface of a substrate; Among them, the base layer includes adhesive resin, positively charged polymer, filler and diluent; the corrosion barrier layer includes flexible polymer resin, negatively charged polymer and two-dimensional nanosheets; the connecting layer includes adhesive resin, positively charged polymer, filler and connecting agent; the flexible antifouling layer includes flexible polymer resin and temperature-responsive polymer microcapsules encapsulating antifouling agent; the positively charged polymer includes any one of polyvinyl alcoholamine, polyaniline, polymethacryloyloxyethyltrimethylammonium chloride, polyacrylamide or a combination of two or more thereof; the negatively charged polymer includes any one of polyglutamic acid, polyvinyl alcohol acid, sodium polybenzene sulfonate or a combination of two or more thereof.
[0005] The embodiment of the present invention also provides a method for preparing the aforementioned anti-corrosion, anti-fouling and drag-reducing composite coating, which comprises: Applying a first base liquid containing at least an adhesive resin, a positively charged polymer, a filler, and a diluent to the surface of a substrate and subjecting the substrate to a first curing treatment to form a base layer having a multi-level micro-nano structure; Applying a second base liquid containing at least a polymer resin, a negatively charged polymer, two-dimensional nanosheets and a diluent to the surface of the base layer and performing a second curing treatment to form a corrosion barrier layer; Applying a third base liquid containing at least an adhesive resin, a positively charged polymer, a filler, a connector and a diluent to the surface of the corrosion barrier layer and performing a third curing treatment to form a connecting layer; And, a fourth base liquid containing at least a flexible polymer resin, a temperature-responsive polymer microcapsule encapsulating an antifouling agent and a solvent is applied to the surface of the connecting layer and subjected to a fourth curing treatment to form a flexible antifouling layer, thereby obtaining an anticorrosion, antifouling and drag-reducing composite coating.
[0006] The embodiments of the present invention also provide the use of the aforementioned anti-corrosion, anti-fouling and drag-reducing composite coating in the protection of the surface of a ship hull, a pipeline, an offshore platform or an underwater structure.
[0007] Compared with the prior art, the beneficial effects of the present invention are as follows: the anti-corrosion, anti-fouling and drag-reducing composite coating provided by the present invention optimizes the comprehensive performance by effectively coupling multiple functional layers; each functional layer achieves independent regulation through fine segmentation while retaining the original function, and utilizes the characteristics of charged polymers and small molecules of linkers to establish strong interface bonding between the substrate and each functional layer, thereby achieving integrity; at the same time, the preparation method adopted by the present invention has the advantages of a wide range of applicability and large-area coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0009] Figure 1 It is a schematic diagram of the structure of the anti-corrosion, anti-fouling and drag-reducing composite coating in a typical implementation scheme of the present invention.
[0010] Explanation of reference numerals: 1 - substrate, 2 - base layer, 3 - corrosion barrier layer, 4 - connecting layer, 5 - flexible antifouling layer. DETAILED DESCRIPTION
[0011] In view of the defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0012] Specifically, as one aspect of the technical solution of the present invention, an anti-corrosion, anti-fouling and drag-reducing composite coating includes: a base layer, a corrosion barrier layer, a connecting layer and a flexible anti-fouling layer sequentially formed on the surface of a substrate; Among them, the base layer includes adhesive resin, positively charged polymer, filler and diluent; the corrosion barrier layer includes flexible polymer resin, negatively charged polymer and two-dimensional nanosheets; the connecting layer includes adhesive resin, positively charged polymer, filler and connecting agent; the flexible antifouling layer includes flexible polymer resin and temperature-responsive polymer microcapsules encapsulating antifouling agent; the positively charged polymer includes any one of polyvinyl alcoholamine, polyaniline, polymethacryloyloxyethyltrimethylammonium chloride, polyacrylamide or a combination of two or more thereof; the negatively charged polymer includes any one of polyglutamic acid, polyvinyl alcohol acid, sodium polybenzene sulfonate or a combination of two or more thereof.
[0013] Specifically, in the present invention, multiple functional layers are compounded to retain each function while separating and independently regulating each functional factor. Through charged polymers and small linker molecules, strong interface bonding forces are generated between the substrate and each functional layer, unifying each functional layer into an overall structural layer. Among them, the base layer mainly provides interface bonding with the substrate, and suitable materials can be selected according to different substrates; the corrosion barrier layer mainly forms a dense barrier layer through the organic coordination of two-dimensional nanosheets and flexible polymers to reduce the diffusion of corrosive media; the strong interface bonding of the connecting layer at the corrosion barrier layer and the flexible layer also synergistically enhances the corrosion barrier property and further improves the corrosion resistance. The surface flexible layer has the ability to absorb and release deformation energy. When subjected to external force, it can effectively absorb and release energy, thereby reducing fluid resistance. It helps to reduce the friction of the coating in a fluid environment and improve its efficiency.
[0014] In some preferred embodiments, the thickness of the base layer is 20-60 μm.
[0015] In some preferred embodiments, the corrosion barrier layer has a thickness of 0.3-0.5 mm.
[0016] In some preferred embodiments, the thickness of the connecting layer is 20-60 μm.
[0017] In some preferred embodiments, the thickness of the flexible antifouling layer is 0.2-0.5 mm.
[0018] In some preferred embodiments, the method for preparing the temperature-responsive polymer microcapsules encapsulating the antifouling agent comprises: The aqueous phase solution containing dispersed shaped core particles is mixed with the oil phase solution containing temperature-responsive polymer monomer, crosslinking agent and initiator, and emulsified polymerized at 50-80°C for 12-24h, and then centrifuged and dried to obtain microcapsules; Furthermore, the microcapsules are added into a solution containing an antifouling agent and mixed thoroughly, and then stirred, centrifuged and dried to obtain temperature-responsive polymer microcapsules encapsulating the antifouling agent.
[0019] Further, the temperature responsive polymer monomer includes N-isopropylacrylamide and / or a block polymer containing N-isopropylacrylamide, but is not limited thereto.
[0020] Furthermore, the antifouling agent includes any one of copper pyrithione, zinc pyrithione, chitosan or a combination of two or more thereof, but is not limited thereto.
[0021] Further, the cross-linking agent includes any one or a combination of two or more of N,N'-methylenebisacrylamide (MBA), divinylbenzene, and diisocyanate, but is not limited thereto.
[0022] Further, the initiator includes any one or a combination of two or more of potassium persulfate (KPS), azobisisobutyronitrile (AIBN), dimethyl azobisisobutyrate (AIBME), and azobisisoheptanenitrile, but is not limited thereto.
[0023] Furthermore, the nucleation particles include gas phase hydrophobic SiO 2 , Gas phase hydrophilic SiO 2 、TiO 2 、Al 2 O 3 Any one or a combination of two or more thereof, and not limited thereto.
[0024] Furthermore, the volume ratio of the aqueous phase solution to the oil phase solution is 1:4 to 1:2.
[0025] In some more specific embodiments, the structural schematic diagram of the anti-corrosion, anti-fouling and drag-reducing composite coating is as follows: Figure 1 As shown, it includes a substrate 1, a base layer 2, a corrosion barrier layer 3, a connecting layer 4, and a flexible antifouling layer 5.
[0026] The anti-corrosion, anti-fouling and drag-reducing composite coating provided by the present invention is an anti-corrosion and drag-reducing integrated coating with a multi-layer structure, wherein the base layer can improve the bonding strength between the coating and the base; the corrosion barrier layer can provide corrosion barrier and improve the corrosion protection performance of the coating; the presence of the connecting layer can improve the adhesion performance of the flexible anti-fouling layer; the flexible anti-fouling layer provides anti-fouling and drag-reducing performance; at the same time, the preparation method adopted by the present invention has the advantages of wide application range and large-area coating.
[0027] Another aspect of the embodiments of the present invention further provides a method for preparing the aforementioned anti-corrosion, anti-fouling and drag-reducing composite coating, which comprises: Applying a first base liquid containing at least an adhesive resin, a positively charged polymer, a filler, and a diluent to the surface of a substrate and subjecting the substrate to a first curing treatment to form a base layer having a multi-level micro-nano structure; Applying a second base liquid containing at least a polymer resin, a negatively charged polymer, two-dimensional nanosheets and a diluent to the surface of the base layer and performing a second curing treatment to form a corrosion barrier layer; Applying a third base liquid containing at least an adhesive resin, a positively charged polymer, a filler, a connector and a diluent to the surface of the corrosion barrier layer and performing a third curing treatment to form a connecting layer; And, a fourth base liquid containing at least a flexible polymer resin, a temperature-responsive polymer microcapsule encapsulating an antifouling agent and a solvent is applied to the surface of the connecting layer and subjected to a fourth curing treatment to form a flexible antifouling layer, thereby obtaining an anticorrosion, antifouling and drag-reducing composite coating.
[0028] In some preferred embodiments, the preparation method specifically comprises: applying the first base liquid to the surface of the substrate by spraying or brushing and curing it at room temperature for 12 to 24 hours to form a base layer with a multi-level micro-nano structure. In the present invention, the multi-level structure is prepared by using mixed-scale fillers.
[0029] In some preferred embodiments, the preparation method specifically comprises: applying the second base liquid to the surface of the base layer by spraying or brushing and curing it at room temperature for 4 to 12 hours to form a corrosion barrier layer.
[0030] In some preferred embodiments, the preparation method specifically comprises: applying the third base liquid to the surface of the corrosion barrier layer by spraying or brushing and curing it at room temperature for 12 to 24 hours to form a connecting layer.
[0031] In some preferred embodiments, the preparation method specifically comprises: applying the fourth base liquid to the surface of the connecting layer by spraying or brushing and curing it at room temperature for 12 to 24 hours to form a flexible antifouling layer.
[0032] In some preferred embodiments, the mass ratio of the adhesive resin, the positively charged polymer, the filler and the diluent in the first base liquid is 20-50:0.5-5:0.5-5:0-30.
[0033] In some preferred embodiments, the mass ratio of the flexible polymer resin, the negatively charged polymer, the two-dimensional nanosheets and the diluent in the second base liquid is 20-50: 0.5-5: 0.5-5: 0-30.
[0034] In some preferred embodiments, the mass ratio of the adhesive resin, the positively charged polymer, the filler, the connector and the diluent in the third base liquid is 10-50: 0.5-5: 0.5-5: 0.5-5: 0-30.
[0035] In some preferred embodiments, the mass ratio of the flexible polymer resin, the temperature-responsive polymer microcapsules encapsulating the antifouling agent, and the solvent in the fourth base liquid is 30-50:1-5:0-30.
[0036] In some preferred embodiments, the adhesive resin includes any one or a combination of two or more of modified epoxy resin, epoxy zinc-rich primer, acrylic polyurethane paint, amino silicone resin, and polyurethane-modified epoxy resin, and is not limited thereto.
[0037] In some preferred embodiments, the filler includes any one or a combination of two or more of kaolin, talc, mica powder, zinc oxide, titanium dioxide, silicon dioxide, glass beads, and diatomaceous earth, but is not limited thereto.
[0038] In some preferred embodiments, the particle size of the filler is 0.01-20 μm.
[0039] In some preferred embodiments, the filler includes micron-sized fillers and nano-sized fillers.
[0040] In some preferred embodiments, the diluent includes any one or a combination of two or more of toluene, xylene, ethanol, ethyl acetate, butyl acetate, propylene glycol methyl ether, and formamide, and is not limited thereto.
[0041] In some preferred embodiments, the polymer resin includes any one or a combination of two or more of epoxy resin, phenolic epoxy resin, polyurethane formate, methyl methacrylate resin, and acrylic resin, and is not limited thereto.
[0042] In some preferred embodiments, the two-dimensional nanosheet includes any one or a combination of two or more of BN, graphene, graphene oxide, MXene, and tungsten disulfide, but is not limited thereto.
[0043] In some preferred embodiments, the two-dimensional nanosheet has a sheet diameter of 1 to 30 μm.
[0044] In some preferred embodiments, the linking agent includes any one or a combination of two or more of isocyanatepropyl triethoxysilane, 3-(isobutyleneoxy)propyl trimethoxysilane, aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, divinyl triaminopropyl trimethoxysilane, and vinyl triethoxysilane, and is not limited thereto.
[0045] In some preferred embodiments, the flexible polymer resin includes any one or a combination of two or more of silicone resin, polyurethane, acrylic modified silicone resin, and polyurea, but is not limited thereto.
[0046] In some preferred embodiments, the solvent includes any one or a combination of two or more of toluene, xylene, ethyl acetate, acetone, ethanol, butanol, and butyl acetate, and is not limited thereto.
[0047] In some preferred embodiments, the substrate includes any one of a steel substrate, an aluminum alloy substrate, and a copper alloy substrate, or a combination of two or more thereof, and is not limited thereto.
[0048] Another aspect of the embodiments of the present invention further provides the use of the aforementioned anti-corrosion, anti-fouling and drag-reducing composite coating in the protection of the surface of a hull, a pipeline, an offshore platform or an underwater structure.
[0049] In the present invention, the base layer selects appropriate materials according to the characteristics of different substrates to enhance the stable interface bonding between the coating and the substrate; and the corrosion barrier layer achieves a strong barrier effect on corrosion factors through the organic combination of resin and two-dimensional sheet materials. In addition, the connecting layer and the flexible antifouling layer can further temperature-responsive antifouling microcapsules to enhance the corrosion protection performance of the coating; the presence of the connecting layer can improve the adhesion performance of the flexible antifouling layer; the flexible antifouling layer is composited with flexible materials and temperature-responsive antifouling microcapsules, and the introduction of this layer enables the coating to effectively absorb and release energy when facing deformation, thereby significantly reducing the resistance encountered by the fluid during movement. In addition, through the composite temperature-responsive antifouling microcapsules, the coating can intelligently control the release of the antifouling agent according to temperature changes, thereby enhancing the overall antifouling performance of the coating and achieving the effect of antifouling and drag reduction; at the same time, the preparation method adopted by the present invention has the advantages of a wide range of applications and large-area coating.
[0050] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0051] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.
[0052] Example 1 (1) 70 wt.% epoxy zinc-rich primer, 5 wt.% polyvinyl alcoholamine, 2.5 wt.% talcum powder and 2.5 wt.% nano-SiO 2 Dissolve in butyl acetate and mix evenly to obtain a first base liquid; apply the base liquid on the surface of the substrate and cure it at room temperature for 8 hours to form a base layer; (2) Dissolving 70 wt.% of a single-component high-elastic silicone resin, 5 wt.% of polyvinyl alcohol acid, and 5 wt.% of nano-BN in butyl acetate, and uniformly stirring the mixture mechanically to obtain a second base liquid; applying the base liquid in situ on the surface of the above-mentioned base layer, and curing the base liquid at room temperature for 12 hours to form a corrosion barrier layer; (3) 60 wt.% of silicone resin, 10 wt.% of 3-(isobutyleneoxy)propyltrimethoxysilane, 5 wt.% of polyvinyl alcoholamine, and 10 wt.% of talc are dissolved in butyl acetate and uniformly stirred mechanically to obtain a third base liquid; the base liquid is applied in situ to the above-mentioned corrosion barrier layer and cured at room temperature for 8 hours to form a connecting layer; (4) 70 wt.% of a single-component high-elastic silicone resin and 10 wt.% of a temperature-responsive polymer microcapsule encapsulating an antifouling agent are dissolved in xylene and uniformly stirred mechanically to obtain a fourth base liquid; the base liquid is applied in situ to the surface of the above-mentioned connecting layer and cured at room temperature for 12 h to obtain an anti-corrosion, anti-fouling and drag-reducing composite coating.
[0053] The preparation method of the temperature-responsive polymer microcapsules encapsulating the antifouling agent is as follows: 1.5 g of fumed hydrophobic SiO 2 The particles (30 nm) were dispersed in 100 ml of deionized water to prepare the water phase, and 10 ml of N-isopropylacrylamide (NIPAM), 0.5 ml of N,N'-methylenebisacrylamide (MBA), and 0.2 ml of azobisisobutyronitrile (AIBN) were added to 50 ml of xylene to prepare the oil phase. The water and oil phases were mixed at a volume ratio of 1 / 3, stirred at high speed for 12 hours at 50 ° C, centrifuged, and dried to obtain poly (N-isopropylacrylamide) microcapsule particles. 1 g of the above microcapsule particles was added to 40 g / L 2-pyridinethione copper ethanol solution and mixed thoroughly. After stirring for 12 hours, centrifuged and dried to obtain temperature-responsive polymer microcapsules encapsulating antifouling agents.
[0054] Example 2 (1) dissolving 70 wt.% of methyl methacrylate, 5 wt.% of polyvinyl alcoholamine, 2.5 wt.% of micron zinc oxide and 2.5 wt.% of nano zinc oxide in toluene to obtain a first base liquid; applying the base liquid on the surface of the substrate and curing it at room temperature for 12 hours to form a base layer; (2) dissolving 70 wt.% phenolic epoxy resin, 5 wt.% sodium polybenzene sulfonate and 5 wt.% flake graphene in toluene, and uniformly stirring the mixture mechanically to obtain a second base liquid; applying the base liquid in situ on the surface of the substrate, and curing the base liquid at room temperature for 12 hours to form a corrosion barrier layer; (3) 60 wt.% of silicone resin, 10 wt.% of isocyanatepropyl triethoxysilane, 5 wt.% of polyaniline, and 10 wt.% of flake graphene are dissolved in butyl acetate and uniformly stirred mechanically to obtain a third base liquid; the base liquid is in-situ brushed on the above-mentioned corrosion barrier layer, and cured at room temperature for 8 hours to form a connecting layer; (4) 70 wt.% of a single-component high-elastic polyurethane resin and 10 wt.% of a temperature-responsive polymer microcapsule encapsulating an antifouling agent are dissolved in toluene and uniformly stirred by mechanical stirring to obtain a fourth base liquid; the base liquid is applied in situ on the surface of the above-mentioned connecting layer and cured at room temperature for 12 h to obtain an anti-corrosion, anti-fouling and drag-reducing composite coating.
[0055] The preparation method of the temperature-responsive polymer microcapsules encapsulating the antifouling agent is as follows: 1.5 g of fumed hydrophobic SiO 2 The particles (30 nm) were dispersed in 100 ml of deionized water to prepare the water phase, and 10 ml of N-isopropylacrylamide (NIPAM), 0.5 ml of N,N'-methylenebisacrylamide (MBA), and 0.2 ml of azobisisobutyronitrile (AIBN) were added to 50 ml of xylene to prepare the oil phase. The water and oil phases were mixed at a volume ratio of 1 / 3, stirred at high speed for 12 hours at 50 ° C, centrifuged, and dried to obtain poly (N-isopropylacrylamide) microcapsule particles. 1 g of the above microcapsule particles was added to 40 g / L 2-pyridinethione copper ethanol solution and mixed thoroughly. After stirring for 12 hours, centrifuged and dried to obtain temperature-responsive polymer microcapsules encapsulating antifouling agents.
[0056] Example 3 (1) dissolving 70 wt.% acrylic resin, 5 wt.% polyacrylamide, 2.5 wt.% micron silicon dioxide and 2.5 wt.% nano silicon dioxide particles in toluene to obtain a first base liquid; applying the base liquid on the surface of the substrate and curing it at room temperature for 8 hours to form a base layer; (2) dissolving 70 wt.% epoxy resin, 5 wt.% sodium polybenzene sulfonate and 5 wt.% flake graphene in toluene, and uniformly stirring the mixture mechanically to obtain a second base liquid; applying the base liquid in situ on the surface of the substrate, and curing the base liquid at room temperature for 6 hours to form a corrosion barrier layer; (3) 60 wt.% acrylic polyurethane paint, 10 wt.% diethylenetriaminopropyltrimethoxysilane, 5 wt.% polyacrylamide, and 10 wt.% graphene oxide are dissolved in butyl acetate and uniformly stirred mechanically to obtain a third base liquid; the base liquid is applied in situ to the above-mentioned corrosion barrier layer and cured at room temperature for 8 hours to form a connecting layer; (4) 70 wt.% of a single-component high-elastic polyurea resin and 10 wt.% of a temperature-responsive polymer microcapsule encapsulating an antifouling agent are dissolved in toluene and uniformly stirred by mechanical stirring to obtain a fourth base liquid; the base liquid is applied in situ on the surface of the above-mentioned connecting layer and cured at room temperature for 12 h to obtain an anti-corrosion, anti-fouling and drag-reducing composite coating.
[0057] The preparation method of the temperature-responsive polymer microcapsules encapsulating the antifouling agent is as follows: 1.5 g of fumed hydrophobic SiO 2The particles (30 nm) were dispersed in 100 ml of deionized water to prepare the water phase, and 10 ml of N-isopropylacrylamide (NIPAM), 0.5 ml of N,N'-methylenebisacrylamide (MBA), and 0.2 ml of azobisisobutyronitrile (AIBN) were added to 50 ml of xylene to prepare the oil phase. The water and oil phases were mixed at a volume ratio of 1 / 3, stirred at high speed for 12 hours at 50 ° C, centrifuged, and dried to obtain poly (N-isopropylacrylamide) microcapsule particles. 1 g of the above microcapsule particles was added to 40 g / L 2-pyridinethione copper ethanol solution and mixed thoroughly. After stirring for 12 hours, centrifuged and dried to obtain temperature-responsive polymer microcapsules encapsulating antifouling agents.
[0058] Comparative Example 1 (Compared with Example 2, lacking a base layer) (1) 70 wt.% of phenolic epoxy resin, 5 wt.% of sodium polybenzene sulfonate and 5 wt.% of flake graphene are dissolved in toluene and uniformly stirred by mechanical stirring to obtain a second base liquid; the base liquid is in situ brushed on the surface of the above-mentioned base layer and cured at room temperature for 12 hours to form a corrosion barrier layer; (2) 60 wt.% of silicone resin, 10 wt.% of isocyanatepropyl triethoxysilane, 5 wt.% of polyaniline, and 10 wt.% of flake graphene are dissolved in butyl acetate and uniformly stirred mechanically to obtain a third base liquid; the base liquid is in-situ brushed on the above-mentioned corrosion barrier layer, and cured at room temperature for 8 hours to form a connecting layer; (3) 70 wt.% of a single-component high-elastic polyurethane resin and 10 wt.% of a temperature-responsive polymer microcapsule encapsulating an antifouling agent are dissolved in toluene and uniformly stirred by mechanical stirring to obtain a fourth base liquid; the base liquid is applied in situ on the surface of the above-mentioned connecting layer and cured at room temperature for 12 hours to obtain a composite coating.
[0059] The preparation method of the temperature-responsive polymer microcapsules encapsulating the antifouling agent is as follows: 1.5 g of fumed hydrophobic SiO 2 The particles (30 nm) were dispersed in 100 ml of deionized water to prepare the water phase, and 10 ml of N-isopropylacrylamide (NIPAM), 0.5 ml of N,N'-methylenebisacrylamide (MBA), and 0.2 ml of azobisisobutyronitrile (AIBN) were added to 50 ml of xylene to prepare the oil phase. The water and oil phases were mixed at a volume ratio of 1 / 3, stirred at high speed for 12 hours at 50 ° C, centrifuged, and dried to obtain poly (N-isopropylacrylamide) microcapsule particles. 1 g of the above microcapsule particles was added to 40 g / L 2-pyridinethione copper ethanol solution and mixed thoroughly. After stirring for 12 hours, centrifuged and dried to obtain temperature-responsive polymer microcapsules encapsulating antifouling agents.
[0060] Performance characterization: The prepared composite coating has weak bonding with the substrate and is easy to fall off.
[0061] Comparative Example 2 (Compared with Example 2, lacking a corrosion barrier layer) (1) dissolving 70 wt.% of methyl methacrylate, 5 wt.% of polyvinyl alcoholamine, 2.5 wt.% of micron zinc oxide and 2.5 wt.% of nano zinc oxide in toluene to obtain a first base liquid; applying the base liquid on the surface of the substrate and curing it at room temperature for 12 hours to form a base layer; (2) 60 wt.% of silicone resin, 10 wt.% of isocyanatepropyl triethoxysilane, 5 wt.% of polyaniline, and 10 wt.% of flake graphene are dissolved in butyl acetate and uniformly stirred mechanically to obtain a third base liquid; the base liquid is applied in situ on the surface of the substrate layer and cured at room temperature for 8 hours to form a connecting layer; (3) 80 wt.% of a single-component high-elastic polyurethane resin and 10 wt.% of a temperature-responsive polymer microcapsule encapsulating an antifouling agent are dissolved in toluene and uniformly stirred by mechanical stirring to obtain a fourth base liquid; the base liquid is applied in situ on the surface of the above-mentioned connecting layer and cured at room temperature for 12 hours to obtain a composite coating.
[0062] The preparation method of the temperature-responsive polymer microcapsules encapsulating the antifouling agent is as follows: 1.5 g of fumed hydrophobic SiO 2 The particles (30 nm) were dispersed in 100 ml of deionized water to prepare the water phase, and 10 ml of N-isopropylacrylamide (NIPAM), 0.5 ml of N,N'-methylenebisacrylamide (MBA), and 0.2 ml of azobisisobutyronitrile (AIBN) were added to 50 ml of xylene to prepare the oil phase. The water and oil phases were mixed at a volume ratio of 1 / 3, stirred at high speed for 12 hours at 50 ° C, centrifuged, and dried to obtain poly (N-isopropylacrylamide) microcapsule particles. 1 g of the above microcapsule particles was added to 40 g / L 2-pyridinethione copper ethanol solution and mixed thoroughly. After stirring for 12 hours, centrifuged and dried to obtain temperature-responsive polymer microcapsules encapsulating antifouling agents.
[0063] Performance characterization: The prepared composite coating has poor corrosion resistance.
[0064] Comparative Example 3 (Compared with Example 2, lacking a connecting layer) (1) dissolving 70 wt.% of methyl methacrylate, 5 wt.% of polyvinyl alcoholamine, 2.5 wt.% of micron zinc oxide and 2.5 wt.% of nano zinc oxide in toluene to obtain a first base liquid; applying the base liquid on the surface of the substrate and curing it at room temperature for 12 hours to form a base layer; (2) dissolving 70 wt.% phenolic epoxy resin, 5 wt.% sodium polybenzene sulfonate and 5 wt.% flake graphene in toluene, and uniformly stirring the mixture mechanically to obtain a second base liquid; applying the base liquid in situ on the surface of the substrate, and curing the base liquid at room temperature for 12 hours to form a corrosion barrier layer; (3) 70 wt.% of a single-component high-elastic polyurethane resin and 10 wt.% of a temperature-responsive polymer microcapsule encapsulating an antifouling agent are dissolved in toluene and uniformly stirred by mechanical stirring to obtain a fourth base liquid; the base liquid is in situ brushed on the surface of the above-mentioned corrosion barrier layer and cured at room temperature for 12 h to obtain an anti-corrosion, anti-fouling and drag-reducing composite coating.
[0065] The preparation method of the temperature-responsive polymer microcapsules encapsulating the antifouling agent is as follows: 1.5 g of fumed hydrophobic SiO 2 The particles (30 nm) were dispersed in 100 ml of deionized water to prepare the water phase, and 10 ml of N-isopropylacrylamide (NIPAM), 0.5 ml of N,N'-methylenebisacrylamide (MBA), and 0.2 ml of azobisisobutyronitrile (AIBN) were added to 50 ml of xylene to prepare the oil phase. The water and oil phases were mixed at a volume ratio of 1 / 3, stirred at high speed for 12 hours at 50 ° C, centrifuged, and dried to obtain poly (N-isopropylacrylamide) microcapsule particles. 1 g of the above microcapsule particles was added to 40 g / L 2-pyridinethione copper ethanol solution and mixed thoroughly. After stirring for 12 hours, centrifuged and dried to obtain temperature-responsive polymer microcapsules encapsulating antifouling agents.
[0066] Performance characterization: The flexible drag reduction layer of the prepared composite coating has a weak bond with the underlying material and is easy to fall off.
[0067] Comparative Example 4 (Compared with Example 2, lacking a flexible drag reduction layer) (1) dissolving 70 wt.% of methyl methacrylate, 5 wt.% of polyvinyl alcoholamine, 2.5 wt.% of micron zinc oxide and 2.5 wt.% of nano zinc oxide in toluene to obtain a first base liquid; applying the base liquid on the surface of the substrate and curing it at room temperature for 12 hours to form a base layer; (2) dissolving 70 wt.% of phenolic epoxy resin, 5 wt.% of sodium polybenzene sulfonate and 5 wt.% of graphene flakes in toluene, and uniformly stirring the mixture mechanically to obtain a second base liquid; applying the base liquid in situ on the surface of the substrate, and curing the base liquid at room temperature for 12 hours to form a corrosion barrier layer; (3) 60 wt.% of silicone resin, 10 wt.% of triethoxypropyl isocyanate, 5 wt.% of polyaniline, and 10 wt.% of flake graphene are dissolved in butyl acetate and uniformly stirred mechanically to obtain a third base liquid; the base liquid is in situ brushed on the above-mentioned corrosion barrier layer and cured at room temperature for 8 hours to form a composite coating.
[0068] Performance characterization: The prepared composite coating has no drag reduction effect.
[0069] Comparative Example 5 (Compared with Example 2, lacking the temperature-responsive polymer microcapsules encapsulating the antifouling agent) (1) dissolving 70 wt.% of methyl methacrylate, 5 wt.% of polyvinyl alcoholamine, 2.5 wt.% of micron zinc oxide and 2.5 wt.% of nano zinc oxide in toluene to obtain a first base liquid; applying the base liquid on the surface of the substrate and curing it at room temperature for 12 hours to form a base layer; (2) dissolving 70 wt.% phenolic epoxy resin, 5 wt.% sodium polybenzene sulfonate and 5 wt.% flake graphene in toluene, and uniformly stirring the mixture mechanically to obtain a second base liquid; applying the base liquid in situ on the surface of the substrate, and curing the base liquid at room temperature for 12 hours to form a corrosion barrier layer; (3) 60 wt.% of silicone resin, 10% of triethoxypropyl isocyanate silane, 5 wt.% of polyaniline, and 10 wt.% of graphene flakes are dissolved in butyl acetate and uniformly stirred mechanically to obtain a third base liquid; the base liquid is in-situ brushed on the above-mentioned corrosion barrier layer and cured at room temperature for 8 hours to form a connecting layer; (4) 80 wt.% of a single-component high-elastic polyurethane resin is dissolved in toluene and uniformly stirred by mechanical stirring to obtain a fourth base liquid; the base liquid is applied in situ to the surface of the above-mentioned connecting layer and cured at room temperature for 12 hours to obtain an anti-corrosion, anti-fouling and drag-reducing composite coating.
[0070] Performance characterization: The prepared composite coating has poor antifouling effect.
[0071] Comparative Example 6 (Compared with Example 2, lacking two-dimensional nanosheets) (1) dissolving 70 wt.% of methyl methacrylate, 5 wt.% of polyvinyl alcoholamine, 2.5 wt.% of micron zinc oxide and 2.5 wt.% of nano zinc oxide in toluene to obtain a first base liquid; applying the base liquid on the surface of the substrate and curing it at room temperature for 12 hours to form a base layer; (2) dissolving 70 wt.% phenolic epoxy resin and 5 wt.% sodium polybenzene sulfonate in toluene, and uniformly stirring the mixture mechanically to obtain a second base liquid; applying the base liquid in situ on the surface of the substrate layer, and curing the base liquid at room temperature for 12 hours to form a corrosion barrier layer; (3) 60 wt.% of silicone resin, 10% of triethoxypropyl isocyanate silane, and 5 wt.% of polyaniline are dissolved in butyl acetate and uniformly stirred mechanically to obtain a third base liquid; the base liquid is applied in situ to the corrosion barrier layer and cured at room temperature for 8 hours to form a connecting layer; (4) 70 wt.% of a single-component high-elastic polyurethane resin and 10 wt.% of a temperature-responsive polymer microcapsule encapsulating an antifouling agent are dissolved in toluene and uniformly stirred by mechanical stirring to obtain a fourth base liquid; the base liquid is applied in situ on the surface of the above-mentioned connecting layer and cured at room temperature for 12 h to obtain an anti-corrosion, anti-fouling and drag-reducing composite coating.
[0072] The preparation method of the temperature-responsive polymer microcapsules encapsulating the antifouling agent is as follows: 1.5 g of fumed hydrophobic SiO 2 The particles (30 nm) were dispersed in 100 ml of deionized water to prepare the water phase, and 10 ml of N-isopropylacrylamide (NIPAM), 0.5 ml of N,N'-methylenebisacrylamide (MBA), and 0.2 ml of azobisisobutyronitrile (AIBN) were added to 50 ml of xylene to prepare the oil phase. The water and oil phases were mixed at a volume ratio of 1 / 3, stirred at high speed for 12 hours at 50 ° C, centrifuged, and dried to obtain poly (N-isopropylacrylamide) microcapsule particles. 1 g of the above microcapsule particles was added to 40 g / L 2-pyridinethione copper ethanol solution and mixed thoroughly. After stirring for 12 hours, centrifuged and dried to obtain temperature-responsive polymer microcapsules encapsulating antifouling agents.
[0073] Performance characterization: The prepared composite coating has poor corrosion resistance.
[0074] Comparative Example 7 (Compared with Example 2, the base layer lacks polyvinyl alcohol amine, and the corrosion barrier layer lacks sodium polybenzene sulfonate) (1) dissolving 70 wt.% of methyl methacrylate, 2.5 wt.% of micron zinc oxide and 2.5 wt.% of nano zinc oxide in toluene to obtain a first base liquid; applying the base liquid on the surface of the substrate and curing it at room temperature for 12 hours to form a base layer; (2) dissolving 70 wt.% of phenolic epoxy resin and 5 wt.% of flake graphene in toluene, and uniformly stirring the mixture mechanically to obtain a second base liquid; applying the base liquid in situ on the surface of the substrate, and curing the base liquid at room temperature for 12 hours to form a corrosion barrier layer; (3) 60 wt.% of silicone resin, 10 wt.% of isocyanatepropyl triethoxysilane, 5 wt.% of polyaniline, and 10 wt.% of flake graphene are dissolved in butyl acetate and uniformly stirred mechanically to obtain a third base liquid; the base liquid is in-situ brushed on the above-mentioned corrosion barrier layer, and cured at room temperature for 8 hours to form a connecting layer; (4) 70 wt.% of a single-component high-elastic polyurethane resin and 10 wt.% of a temperature-responsive polymer microcapsule encapsulating an antifouling agent are dissolved in toluene and uniformly stirred by mechanical stirring to obtain a fourth base liquid; the base liquid is applied in situ on the surface of the above-mentioned connecting layer and cured at room temperature for 12 h to obtain an anti-corrosion, anti-fouling and drag-reducing composite coating.
[0075] The preparation method of the temperature-responsive polymer microcapsules encapsulating the antifouling agent is as follows: 1.5 g of fumed hydrophobic SiO 2 The particles (30 nm) were dispersed in 100 ml of deionized water to prepare the water phase, and 10 ml of N-isopropylacrylamide (NIPAM), 0.5 ml of N,N'-methylenebisacrylamide (MBA), and 0.2 ml of azobisisobutyronitrile (AIBN) were added to 50 ml of xylene to prepare the oil phase. The water and oil phases were mixed at a volume ratio of 1 / 3, stirred at high speed for 12 hours at 50 ° C, centrifuged, and dried to obtain poly (N-isopropylacrylamide) microcapsule particles. 1 g of the above microcapsule particles was added to 40 g / L 2-pyridinethione copper ethanol solution and mixed thoroughly. After stirring for 12 hours, centrifuged and dried to obtain temperature-responsive polymer microcapsules encapsulating antifouling agents.
[0076] Performance characterization: The prepared composite coating has a degradation in bonding performance:
[0077] Comparative Example 8 (Compared with Example 2, the connecting agent triethoxypropyl isocyanate silane is missing from the connecting layer) (1) 70 wt.% methyl methacrylate, 5 wt.% polyvinyl alcoholamine, 5 wt.% micron zinc oxide and nano zinc oxide are dissolved in toluene to obtain a first base liquid; the base liquid is brushed on the surface of the substrate and cured at room temperature for 12 hours to form a base layer; (2) dissolving 70 wt.% phenolic epoxy resin, 5 wt.% sodium polybenzene sulfonate and 5 wt.% flake graphene in toluene, and uniformly stirring the mixture mechanically to obtain a second base liquid; applying the base liquid in situ on the surface of the substrate, and curing the base liquid at room temperature for 12 hours to form a corrosion barrier layer; (3) Dissolving 60 wt.% of silicone resin, 5 wt.% of polyaniline, and 10 wt.% of graphene flakes in butyl acetate, and uniformly stirring the mixture mechanically to obtain a third base liquid; applying the base liquid in situ to the corrosion barrier layer, and curing the base liquid at room temperature for 8 hours to form a connecting layer; (4) 70 wt.% of a single-component high-elastic polyurethane resin and 10 wt.% of a temperature-responsive polymer microcapsule encapsulating an antifouling agent are dissolved in toluene and uniformly stirred by mechanical stirring to obtain a fourth base liquid; the base liquid is applied in situ on the surface of the above-mentioned connecting layer and cured at room temperature for 12 h to obtain an anti-corrosion, anti-fouling and drag-reducing composite coating.
[0078] The preparation method of the temperature-responsive polymer microcapsules encapsulating the antifouling agent is as follows: 1.5 g of fumed hydrophobic SiO 2 The particles (30 nm) were dispersed in 100 ml of deionized water to prepare the water phase, and 10 ml of N-isopropylacrylamide (NIPAM), 0.5 ml of N,N'-methylenebisacrylamide (MBA), and 0.2 ml of azobisisobutyronitrile (AIBN) were added to 50 ml of xylene to prepare the oil phase. The water and oil phases were mixed at a volume ratio of 1 / 3, stirred at high speed for 12 hours at 50 ° C, centrifuged, and dried to obtain poly (N-isopropylacrylamide) microcapsule particles. 1 g of the above microcapsule particles was added to 40 g / L 2-pyridinethione copper ethanol solution and mixed thoroughly. After stirring for 12 hours, centrifuged and dried to obtain temperature-responsive polymer microcapsules encapsulating antifouling agents.
[0079] Performance characterization: The prepared composite coating has reduced bonding strength. The composite coatings provided in the comparative examples and embodiments of the present invention were subjected to performance tests, wherein the adhesion test standard is GB / T5210-2006, and the salt spray test standard is GB / T10125-1997. The specific test results are shown in Table 1 below: Table 1 Properties of the coatings prepared in Examples 1-3 and Comparative Examples 1-8 ; In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0080] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.
Claims
1. An anti-corrosion, anti-fouling and drag-reducing composite coating, characterized in that: include: A base layer, a corrosion barrier layer, a connecting layer and a flexible antifouling layer are sequentially formed on the surface of the substrate; Among them, the base layer includes adhesive resin, positively charged polymer, filler and diluent; the corrosion barrier layer includes flexible polymer resin, negatively charged polymer and two-dimensional nanosheets; the connecting layer includes adhesive resin, positively charged polymer, filler and connecting agent; the flexible antifouling layer includes flexible polymer resin and temperature-responsive polymer microcapsules encapsulating antifouling agent; the positively charged polymer includes any one of polyvinyl alcoholamine, polyaniline, polymethacryloyloxyethyltrimethylammonium chloride, polyacrylamide or a combination of two or more thereof; the negatively charged polymer includes any one of polyglutamic acid, polyvinyl alcohol acid, sodium polybenzene sulfonate or a combination of two or more thereof.
2. The anti-corrosion, anti-fouling and drag-reducing composite coating according to claim 1, characterized in that: The thickness of the base layer is 20-60 μm; and / or the thickness of the corrosion barrier layer is 0.3-0.5 mm; and / or the thickness of the connecting layer is 20-60 μm; and / or the thickness of the flexible antifouling layer is 0.2-0.5 mm.
3. The anti-corrosion, anti-fouling and drag-reducing composite coating according to claim 1, characterized in that: The preparation method of the temperature-responsive polymer microcapsule encapsulating the antifouling agent comprises: The aqueous phase solution containing dispersed shaped core particles is mixed with the oil phase solution containing temperature-responsive polymer monomer, crosslinking agent and initiator, and emulsified polymerized at 50-80°C for 12-24h, and then centrifuged and dried to obtain microcapsules; Furthermore, the microcapsules are added into a solution containing an antifouling agent and mixed thoroughly, and then stirred, centrifuged and dried to obtain temperature-responsive polymer microcapsules encapsulating the antifouling agent.
4. The anti-corrosion, anti-fouling and drag-reducing composite coating according to claim 3, characterized in that: The temperature responsive polymer monomer includes N-isopropylacrylamide and / or a block polymer containing N-isopropylacrylamide; And / or, the antifouling agent includes any one of copper pyrithione, zinc pyrithione, chitosan or a combination of two or more thereof; And / or, the cross-linking agent includes any one or a combination of two or more of N,N'-methylenebisacrylamide, divinylbenzene, and diisocyanate; And / or, the initiator includes any one or a combination of two or more of potassium persulfate, azobisisobutyronitrile, dimethyl azobisisobutyrate, and azobisisoheptanenitrile; And / or, the nucleation particles include any one or a combination of two or more of gas-phase hydrophobic SiO2, gas-phase hydrophilic SiO2, TiO2, and Al2O3; And / or, the volume ratio of the aqueous phase solution to the oil phase solution is 1:4 to 1:
2.
5. The method for preparing the anti-corrosion, anti-fouling and drag-reducing composite coating according to any one of claims 1 to 4, characterized in that: include: Applying a first base liquid containing at least an adhesive resin, a positively charged polymer, a filler, and a diluent to the surface of a substrate and subjecting the substrate to a first curing treatment to form a base layer having a multi-level micro-nano structure; Applying a second base liquid containing at least a polymer resin, a negatively charged polymer, two-dimensional nanosheets and a diluent to the surface of the base layer and performing a second curing treatment to form a corrosion barrier layer; Applying a third base liquid containing at least an adhesive resin, a positively charged polymer, a filler, a connector and a diluent to the surface of the corrosion barrier layer and performing a third curing treatment to form a connecting layer; And, a fourth base liquid containing at least a flexible polymer resin, a temperature-responsive polymer microcapsule encapsulating an antifouling agent and a solvent is applied to the surface of the connecting layer and subjected to a fourth curing treatment to form a flexible antifouling layer, thereby obtaining an anticorrosion, antifouling and drag-reducing composite coating.
6. The preparation method according to claim 5, characterized in that: The multi-level micro-nano structure includes a micron-level peak-valley structure and a nano-level structure covering a micron-level surface; the scale of the micron-level peak-valley structure is 20-100 μm, and the scale of the nano-level structure is 30-300 nm.
7. The preparation method according to claim 5, characterized in that: Specifically include: Applying the first base liquid to the surface of the substrate by spraying or brushing and curing at room temperature for 12 to 24 hours to form a base layer with a multi-level micro-nano structure; and / or, applying the second base liquid to the surface of the base layer by spraying or brushing and curing it at room temperature for 4 to 12 hours to form a corrosion barrier layer; and / or, applying the third base liquid to the surface of the corrosion barrier layer by spraying or brushing and curing it at room temperature for 12 to 24 hours to form a connecting layer; And / or, the fourth base liquid is applied to the surface of the connecting layer by spraying or brushing and cured at room temperature for 12 to 24 hours to form a flexible antifouling layer.
8. The preparation method according to claim 5, characterized in that: The mass ratio of the adhesive resin, the positively charged polymer, the filler and the diluent in the first base liquid is 20-50: 0.5-5: 0.5-5: 0-30; And / or, the mass ratio of the flexible polymer resin, the negatively charged polymer, the two-dimensional nanosheets and the diluent in the second base liquid is 20-50: 0.5-5: 0.5-5: 0-30; And / or, the mass ratio of the adhesive resin, the positively charged polymer, the filler, the connector and the diluent in the third base liquid is 10-50: 0.5-5: 0.5-5: 0.5-5: 0-30; And / or, the mass ratio of the flexible polymer resin, the temperature-responsive polymer microcapsules encapsulating the antifouling agent, and the solvent in the fourth base liquid is 30-50:1-5:0-30.
9. The preparation method according to claim 5, characterized in that: The adhesive resin includes any one or a combination of two or more of modified epoxy resin, epoxy zinc-rich primer, acrylic polyurethane paint, amino silicone resin, and polyurethane modified epoxy resin; And / or, the filler comprises any one or a combination of two or more of kaolin, talc, mica powder, zinc oxide, titanium dioxide, silicon dioxide, glass beads, and diatomaceous earth; and / or, the particle size of the filler is 0.01-20 μm; and / or, the filler comprises a micron-grade filler and a nano-grade filler; And / or, the diluent includes any one or a combination of two or more of toluene, xylene, ethanol, ethyl acetate, butyl acetate, propylene glycol methyl ether, and formamide; And / or, the polymer resin includes any one or a combination of two or more of epoxy resin, phenolic epoxy resin, polyurethane formate, methyl methacrylate resin, and acrylic resin; And / or, the two-dimensional nanosheets include any one or a combination of two or more of BN, graphene, graphene oxide, MXene, and tungsten disulfide; And / or, the size of the two-dimensional nanosheet is 1-30 μm; And / or, the linking agent includes any one or a combination of two or more of isocyanatepropyl triethoxysilane, 3-(isobutyleneoxy)propyl trimethoxysilane, aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, divinyl triaminopropyl trimethoxysilane, and vinyl triethoxysilane; And / or, the flexible polymer resin includes any one or a combination of two or more of silicone resin, polyurethane, acrylic modified silicone resin, and polyurea; And / or, the solvent includes any one or a combination of two or more of toluene, xylene, ethyl acetate, acetone, ethanol, butanol, and butyl acetate; And / or, the substrate includes any one of a steel substrate, an aluminum alloy substrate, and a copper alloy substrate, or a combination of two or more thereof.
10. Use of the anti-corrosion, anti-fouling and drag-reducing composite coating according to any one of claims 1 to 4 in the surface protection of a ship hull, a pipeline, an offshore platform or an underwater structure.
Citation Information
Patent Citations
Article having antifouling properties for aquatic and particularly sea use
CN102076789A
Anti-icing composite coating and manufacturing method thereof
CN102205680A
Preparation process for thermosensitive controlled-release material for marine antifouling agent
CN102726382A
Biocidal foul release coating systems
CN103608411A
Curable organopolysiloxane anti-fouling composite coating, and anti-fouling substrate coated with the composite coating
CN104768746A
Cited By
Self-adaptive resistance and noise reduction composite coating as well as preparation method and application thereof
CN121450205A